2016
DOI: 10.1094/phyto-02-16-0080-fi
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a Phenotyping Center Revealed by the Genome-Guided Mapping of Powdery Mildew Resistance Loci

Abstract: The genomics era brought unprecedented opportunities for genetic analysis of host resistance, but it came with the challenge that accurate and reproducible phenotypes are needed so that genomic results appropriately reflect biology. Phenotyping host resistance by natural infection in the field can produce variable results due to the uncontrolled environment, uneven distribution and genetics of the pathogen, and developmentally regulated resistance among other factors. To address these challenges, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Thus, with appropriate lighting, as employed by the APS system, the 4-5 휇m in diameter fungal hyphae in nascent colonies of E. necator can be resolved on live samples, using 3× magnification within 48 hours after inoculation. The hyphal transect method represents the previous gold standard for manual quantification of grapevine powdery mildew disease severity [21] and aside from throughput and repeated measures, there are strengths and weaknesses in data quality compared to the APS developed here. The primary weakness of hyphal transects comes from subsampling only along the vertical and horizontal transects, thus missing any fungal growth that occurs away from these lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, with appropriate lighting, as employed by the APS system, the 4-5 휇m in diameter fungal hyphae in nascent colonies of E. necator can be resolved on live samples, using 3× magnification within 48 hours after inoculation. The hyphal transect method represents the previous gold standard for manual quantification of grapevine powdery mildew disease severity [21] and aside from throughput and repeated measures, there are strengths and weaknesses in data quality compared to the APS developed here. The primary weakness of hyphal transects comes from subsampling only along the vertical and horizontal transects, thus missing any fungal growth that occurs away from these lines.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a major effort is underway to genetically map host resistance loci for introgression from wild Vitis into domesticated V. vinifera [17][18][19][20]. In previous studies of host resistance to E. necator and pathogen resistance to fungicides, controlled phenotyping of E. necator on grape leaf tissue used 1-cm diameter circular leaf disks cut from living grape leaves, arrayed on agar within Petri dishes or glass trays [21][22][23]. For host resistance assessment at 2 to 10 days after inoculation, the disks were destructively sampled by bleaching the leaf samples and then staining with a dye to make the hyphae more visible for phenotypic analysis under brightfield microscopy at 100× to 400× [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C2-50 and Riesling SNP sets were reduced to 367 and 403 SNPs, respectively, as described in the material methods and R/OneMap was used to curate and construct the genetic maps. For each SNP set, 19 linkage groups (LGs) were produced and the final size for the C2-50 and Riesling genetic maps were 1587.3 and 1706.4 cM, respectively ( S5 and S6 Tables), which is similar in size to other Vitis genetic maps produced by next generation sequencing [ 23 , 25 , 26 , 28 ]. The map density or average distance between SNP markers for C2-50 and Riesling genetic maps was 4.3 and 4.2 cM, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Partial resistance is conferred by major QTLs found on different chromosomes. Ren2 on chromosome 14 confers race-specific resistance in V. cinerea (Dalbó et al, 2001; Cadle-Davidson et al, 2016). Ren 3 on chromosome 15–derived from an undetermined American Vitis species–was localized in the variety Regent (Welter et al, 2007) and recently found to determine race-specific hypersensitive response by two different regions on that chromosome; in fact, Zendler et al (2017) defined the Ren3 limit and identified ex novo the distal Ren9 locus.…”
Section: Grapevine-ascomycete Interactionmentioning
confidence: 99%